2017
DOI: 10.1039/c7ra07221j
|View full text |Cite
|
Sign up to set email alerts
|

An efficient green-emitting Ba5Si2O6Cl6:Eu2+ phosphor for white-light LED application

Abstract: The present paper reports a new phosphor material for WLED application with high CRI, low CCT and high colour stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…Dutta et al also reported the activation energy of Ba 5 Si 2 O 6 Cl 6 : Eu 2+ phosphors with high thermal stability was around 0.37 eV. In the present case, the high activation energy compared with the above reports was obtained, thereby indicating high thermal stability of the present phosphors …”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Dutta et al also reported the activation energy of Ba 5 Si 2 O 6 Cl 6 : Eu 2+ phosphors with high thermal stability was around 0.37 eV. In the present case, the high activation energy compared with the above reports was obtained, thereby indicating high thermal stability of the present phosphors …”
Section: Resultssupporting
confidence: 71%
“…In the present case, the high activation energy compared with the above reports was obtained, thereby indicating high thermal stability of the present phosphors. 16,19 Figure 4B presents the electroluminescence (EL) spectra of LEDs driven at a current of 280 mA. When Sr 1.906 Ce 0.06 Eu 0.004 Si 5 N 8 was coated on a blue LED chip, the EL spectrum exhibited near white light emission (0.34, 0.34) with the CCT value of 4964 K and R a of 80.…”
Section: Resultsmentioning
confidence: 99%
“…White light emitting diodes (wLEDs) have been widely used in daily life due to their eco‐friendly properties, easy fabrication, high efficiency, low cost, and long luminescent lifetime . The traditional wLEDs are prepared by combining a blue LED chip with yellow‐emitting Y 3 Al 5 O 12 : Ce 3+ (YAG: Ce 3+ ) phosphors . Another approach for producing wLEDs is via combining red‐, green‐, and blue‐emitting phosphors with a near ultraviolet (NUV) LED chip .…”
Section: Introductionmentioning
confidence: 99%
“…The halide ion could strongly coordinate with activator ions and therefore enhance the crystal‐field splitting (CFS) of Eu 2+ ions. Dutta and Chen synthesized green‐emitting Ba 5 Si 2 O 6 Cl 6 :Eu 2+ (BSOC:Eu 2+ ) phosphors . The luminescence studies revealed that increasing the concentration of Eu 2+ ion brought changes in the lattice parameters of the Ba 5 Si 2 O 6 Cl 6 that increased CFS, as shown in Figure .…”
Section: Development Of New Phosphorsmentioning
confidence: 83%